2018
DOI: 10.3169/mta.6.195
|View full text |Cite
|
Sign up to set email alerts
|

[Papers] Single Exposure Type Wide Dynamic Range CMOS Image Sensor With Enhanced NIR Sensitivity

Abstract: In new markets such as in-vehicle cameras, surveillance camera and sensing applications that are rising rapidly in recent years, there is a growing need for better NIR sensing capability for clearer night vision imaging, in addition to wider dynamic range imaging without motion artifacts and higher signal-to-noise (S/N) ratio, especially in low-light situation. We have improved the previously reported single exposure type wide dynamic range CMOS image sensor (CIS), by optimizing the optical structure such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The authors reported an over 87 dB SEHDR CIS with a 3.0 µm pixel introducing a high full-well capacity (FWC) photodiode (PD) and a multiple gain pixel technology [1][2][3][4]. In the previous sensor, photoelectrons accumulated in the photodiode are read out two times in different gains, then combined into an HDR signal.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported an over 87 dB SEHDR CIS with a 3.0 µm pixel introducing a high full-well capacity (FWC) photodiode (PD) and a multiple gain pixel technology [1][2][3][4]. In the previous sensor, photoelectrons accumulated in the photodiode are read out two times in different gains, then combined into an HDR signal.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some all-pixel PDAF CISs with the dual-PD type pixel [27]- [31] Additionally, a near infrared (NIR) enhancement technology [32] was employed for these two types of top layer pixels.…”
Section: A Pdaf Dual Cg Vmgs Pixelmentioning
confidence: 99%